Simulation Of Lightwave Propagation In Photonic Devices - Yusoff, Mohd Hanapiah Mohd (2010)
This dissertation focuses on the simulation of lightwave propagation in planar devices, which include investigation of single mode conditions in rib waveguide, designs of compact silica polarization rotator and splitters, investigation of multiple reflections in photonic crystal (PhC) multimode interference couplers and design of hybrid 1-D and 2-D PhC wavelength division multiplexers and channels interleavers. In the design approach, we have adopted semi-analytical technique which allows us to incorporate fast optimization process. Global and local simplex search techniques were extensively used. In the investigation of single mode conditions in rib waveguide and the design of silica polarization rotator, full vectorial film mode matching and finite element methods were used. Propagation analysis in the silica polarization rotator was conducted using finite element eigen-mode expansion method. The quasi 2-D effective index method with eigen mode expansion method was used in the design of compact silica grating waveguide polarization splitter, investigation of multiple reflections in hybrid PhC multimode interference coupler and design of hybrid PhC wavelength division multiplexers and channel interleavers.